PENAMBAHAN EKSTRAK TEH TERHADAP KARAKTERISTI MIE BASAH - Fungki Sri Rejeki; Diana Puspitasari; Endang Retno Wedowati (Journal of Research and Technology, 2018)
Wet noodles as a source of carbohydrates have a moderate GI value that is 53-56. For this reason, engineering processes was needed to reduce GI value so that it becomes safe and healthy food. Tea (Camellia sinensis) contains tannin polyphenols which can reduce protein and starch digestibility so that the glycemic response decreases. The addition of tea extract to the noodleswill result in changes in product properties, so that research on quality of wet noodles with tea extract addition was needed. This research used Factorial Randomized Block Design. The first factor was tea type with two levels and second factor was tea extract concentration with three levels. The parameters observed were organoleptic test, namely taste, aroma and color, and chemical tests, namely protein and tannin content. The research conclusion were: (1) based on organoleptic test, the addition of green tea was preferred over black tea, (2) the addition of green tea and black tea did not caused significant differences in protein content, (3) the tannin content with the addition of green tea tends to be higher than black tea, and (4) the selected treatmentwas T1K1 (addition of 1% green tea extract) containing 5.81% protein and 15.39% tannin. Keywords: Wet Noodles, Tea Extract, Organoleptic, Protein, Tannin.